Pendampingan dan Penyuluhan Pertanian dalam Meningkatkan Kapasitas Petani Desa Durian Kecamatan Medang Deras Kabupaten Batubara Provinsi Sumatera Utara - Ahya Munawir Pasaribu; Yusra Muharami Lestari (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service program aims to enhance farmers’ capacity through the application of the Rapid Rural Appraisal (RRA) approach in Durian Village. The main problems faced by farmers include limited knowledge and skills in cultivation techniques, suboptimal land utilization, and weak farmer group institutions. The method applied was RRA, consisting of several stages: preparation, rapid data collection through interviews, focus group discussions (FGD), and participatory observation, followed by participatory analysis, joint action planning, program implementation, and monitoring and evaluation.The results show a significant improvement in farmers’ capacity in terms of knowledge, technical skills, and attitudes toward agricultural innovation. Farmers have begun to apply more effective cultivation techniques and optimize land use for potential commodities. In addition, there has been an increase in participation in farmer groups, strengthening of institutional functions, and the emergence of local leaders who act as community mobilizers. The program also fostered collective awareness and behavioral changes toward a more adaptive and sustainable agricultural system. In conclusion, the RRA approach is effective not only in rapidly identifying local problems but also in promoting social change and community capacity building. This community service model has the potential to be replicated in other areas with adjustments to local conditions.